Project VeSElkA: results of abundance analysis for HD 53929 and HD 63975. Issue 3 (15th March 2018) - Ndiaye, M L; LeBlanc, F; Khalack, V
Abstract: Project VeSElkA (Vertical Stratification of Element Abundances) has been initiated with the aim to detect and study the vertical stratification of element abundances in the atmosphere of chemically peculiar stars. Abundance stratification occurs in hydrodynamically stable stellar atmospheres due to the migration of the elements caused by atomic diffusion. Two HgMn stars, HD 53929 and HD 63975, were selected from the VeSElkA sample and analysed with the aim to detect some abundance peculiarities employing the zeeman2 code. We present the results of abundance analysis of HD 53929 and HD 63975 observed recently with the spectropolarimeter ESPaDOnS (Echelle SpectroPolarimetric Device for the Observation of Stars) at Canada–France–Hawaii Telescope. Evidence of phosphorus vertical stratification was detected in the atmosphere of these two stars. In both cases, phosphorus abundance increases strongly towards the superficial layers. The strong overabundance of Mn found in stellar atmosphere of both stars confirms that they are HgMn-type stars.